Mitral valve myxoma associated with intracranial tumor: a case report - Gucu, Arif; Demir, Deniz; Kahraman, Nail; Engin, Mesut; Ozyazicioglu, Ahmet Fatih; Goncu, Mehmet Tugrul (The European Research Journal, 2016)
Primary tumors of the heart are rare, and among them, cardiac myxoma is the most prevalent primary cardiac neoplasm in adult patients. Astrocytoma is the most common glioma and can occur in most parts of the brain and occasionally in the spinal cord. There is a little knowledge about coexistence of cardiac myxoma and astrocytoma in the literature. Cardiac myxoma associated with intracranial tumor is a very rare entity. We presented a case of cardiac myxoma originating mitral anterior valve associated with astrocytoma. The patient underwent the operation for intracranial tumor 2 months before cardiac surgery. Mitral valve myxoma was successfully treated with surgical resection without mitral valve replacement.